(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
This article analyzes the occurrence of very strong (including squally) winds during the cold season in the territory of the Republic of Belarus in a changing climate (from 1989 to 2022). The repeatability, spatial and temporal features of the distribution of such wind from November to March, as well as the trends in the development of a hazardous hydrometeorological phenomenon in a changing climate are presented. In addition to the physical and geographical conditions of weather stations, which affect the spatial and temporal distribution of the phenomenon under study, surface synoptic and high-altitude aerological conditions are determined, contributing to the strengthening of the wind to the criteria of very strong. The main weather recommendations for forecasting very strong (including squally) winds during the cold season are proposed.